Effect of deterioration on critical infrastructure resilience – framework and application on bridges - Davide Forcellini; Stergios-Aristoteles Mitoulis (Results in Engineering)
Realistic assessment of the structural state due to ageing and consequent deterioration of infrastructure is fundamental in assessing its resilience. Yet current methods have not integrated deterioration due to ageing in such assessments. This paper proposes a new framework for the assessment of the effect of deterioration on the resilience of critical infrastructure, with a focus on bridges. The method introduces a three-step process. First, different fit-for purpose materials have been implemented for the calculation of the loss model when the material properties are known. The second step involves the development of hazard-specific fragility models to estimate loss in performance. In the third step, the restoration of the assets is performed to compare the different performance of the configurations which leads to different resilience quantifications. The main outcome of the paper is the quantification of resilience by considering that the speed of recovery is not being affected by the deterioration (Scenario 1). For more realistic resilience assessments, a further scenario (Scenario 2) analyses the role of deterioration in the recovery process, by implementing different capacity reduction rates. The main conclusion of the research is the impact of different levels of deterioration over the years of operation of the bridge. The framework is also applied to estimate the seismic resilience of a bridge with different deterioration scenarios.